.A Critical Review of the Book Entitled Methodology of Religious Studies - Seyed Mohammad Reza Taghavi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The purpose of this study was to criticize the book “Methodology of Religious Studies (New Edition)”, written by Faramarz Gharamlaki in 2013. The book was evaluated from two dimensions of form and content. Formally, the book met most of the requirements and was evaluated favorably. In terms of content, the book contains technical points in most of the book’s chapters which can prepare the reader for research, using the current scientific approaches. Indeed, this book is an extension of the methods accepted in current scientific research. Of course, the author has made great efforts to document the methods using religious texts; however, the base of most parts of the book is the same as the common sciences. To explain the hierarchy of religious science, to set up a methodological system appropriate to Islamic worldview, ontology, and epistemology, a serious effort of religious scholars is needed in order to development of the methodology of Islamic humanities.